İslam Ülkeleri İstatistiksel, Ekonomik ve Sosyal Araştırma ve Eğitim Merkezi (SESRTCIC) Kütüphanesi / Statistical, Economic and Social Research and Traning Centre for Islamic Countries (SESRTCIC) Library - Z. Canan Duran (Bilgi Dünyası, 2005)
The present paper informs in detail the foundation and development of the SESRTCIC Library, together with a thorough explanation of the nature of services being provided